A cross-sectional examination of response inhibition and working memory on the Stroop task - Natasha Duell (2018)
© 2018 Elsevier Inc. The authors examined the association between working memory and response inhibition on the Stroop task using a cross-sectional, international sample of 5099 individuals (49.3% male) ages 10–30 (M = 17.04 years; SD = 5.9). Response inhibition was measured using a Stroop task that included “equal” and “unequal” blocks, during which the relative frequency of neutral and incongruent trials was manipulated. Competing stimuli in incongruent trials evinced inhibitory functioning, and having a lower proportion of incongruent trials (as in unequal blocks) placed higher demands on working memory. Results for accuracy indicated that age and working memory were independently associated with response inhibition. Age differences in response inhibition followed a curvilinear trajectory, with performance improving into early adulthood. Response inhibition was greatest among individuals with high working memory. For response time, age uniquely predicted response inhibition in unequal blocks. In equal blocks, age differences in response inhibition varied as a function of working memory, with age differences being least pronounced among individuals with high working memory. The implications of considering the association between response inhibition and working memory in the context of development are discussed.